Learning Organization And Organizational Climate Influence Employee Performance Mediated By Knowledge Sharing Variables At Pt. Qalin Buana Laras - Septiani, Tria; Wibowo; Karunia, Luki (Jurnal Paradigma Ekonomika, 2025)
This research aims to determine whether Leaning Organization and Organizational Climate affect Employee Performance, mediated by Knowledge Sharing variables at PT. Qalin Buana Laras. The hypotheses proposed in this study are 1) Learning Organization has a significant effect on Employee Performance at PT. Qalin Buana Laras; (2) Organizational Climate has a significant effect on Employee Performance at PT. Qalin Buana Laras; (3) Knowledge Sharing has as significant effect on Employee Performance at PT. Qalin Buana Laras; (4) Learning Organization has a significant effect on Knowledge Sharing at PT. Qalin Buana Laras; (5) Organizational Climate has a significant effect on Knowledge Sharing at PT. Qalin Buana Laras; (6) Learning Organization mediates the effect of Performance on Knowledge Sharing at PT. Qalin Buana Laras; (7) Organizational Climate mediates the effect of Employee Performance on Knowledge Sharing at PT. Qalin Buana Laras. This study uses a quantitative descriptive analysis design. The sampling technique uses Saturated sampling, with 100 respondents. Data collection instruments use questionnaires. The data analysis technique uses BLUE assumption tests (linearity test, normality test, multicollinearity test, autocorrelations test, and heteroscedasticity test) as well as hypothesis tests (regression analysis, coefficient of determination analysis, t-test, and path analysis). The results of this study show the following findings; (1) there is a strong and significant effect between performance and Knowledge Sharing; (2) there is a strong and significant effect between Employee Performance and Learning Organization; (3) there is a very strong and significant effect between Employee Performance and Organizational Climate; (4) there is a strong effect between organizational Learning and Knowledge Sharing; (5) there is a strong relationship between Organizational Climate and Knowledge Sharing; (6) there is an indirect effect in the regression model where Leaning Organization can be a mediating variable between Employee Performance and Knowledge Sharing; (7) there is no indirect effect in the regression model where competence cannot be a mediating variable between Employee Performance and Knowledge Sharing at PT. Qalin Buana Laras.